Vietnam - Indonesia Cooperation on Sea Definition: Practice and Meaning - Ngoc Giap, Tran (VNU Journal of Science: Policy and Management Studies, 2023)
Vietnam has a long coastline and a large sea area, with several islands and archipelagoes, particularly the Hoang Sa and Truong Sa archipelagoes. Therefore, Vietnam's main objectives during the process of national construction and growth are maritime security in particular and the safeguarding of the integrity of its land, sea, and airspace. Vietnam consistently emphasizes cooperation with regional nations to achieve this objective in particular. According to the United Nations Convention on the Law of the Sea 1958, Vietnam shares maritime borders with China and Cambodia, and shares continental shelf boundaries with China, Indonesia, Malaysia, Cambodia and Thailand. Currently, according to the United Nations Convention on the Law of the Sea (UNCLOS) in 1982, the boundary of Vietnam's exclusive economic zone and continental shelf is expanded and adjacent to many countries. Besides the well-defined sea areas with neighboring countries (Thailand, Indonesia), Vietnam is still negotiating some of the remaining sea ares with China, Malaysia and Cambodia. Among the countries with which Vietnam has completed negotiations on maritime delimitation, the cooperation between Vietnam and Indonesia on maritime delimitation is very important, creating a premise for a clearer maritime boundary delimitation with other countries and contributing to promoting the development of the Vietnam - Indonesia Strategic Partnership to a new level. This article will present and analyze the cooperation relationship on maritime delimitation between Vietnam and Indonesia from the perspective of international studies.